Analysis of Understanding of Midwife Students of Midwife Care as the Impact of Online Learning. (2022) - Rahman, Nursyahraeni Madika; Made, Sutina; Usman, Andi Nilawati; Idris, Irfan; Unde, Alimuddin; Bahar, Burhanuddin
No abstract available